Imitation with intention and memory: An experiment - Astrid Matthey (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
Three results emerge from a simple experiment on imitation. First, I find behavior which strongly suggests an intention to imitate. Second, players imitate successful other players rather than repeating successful actions. Third, to find imitation examples, players use several periods of memory. This lends support to learning models with a non-trivial role of memory. The experiment analyzes imitation in an individual learning context. It supplements the results obtained for imitation in evolutionary processes.
Keywords: D01; D83; 330; imitation; learning; memory; experiments